2020
DOI: 10.3233/blc-190249
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Non-muscle Invasive Bladder Cancer Recurrence, Progression, and Mortality: Available Research and Future Directions

Abstract: BACKGROUND: A broad, comprehensive review of studies exploring associations between lifestyle factors and non-muscle invasive bladder cancer (NMIBC) outcomes is warranted to consolidate recommendations and identify gaps in research. OBJECTIVE: To summarize the literature on associations between lifestyle factors and clinical outcomes among patients with NMIBC. METHODS: PubMed was systematically queried for articles published through March 2019 regarding lifestyle factors and recurrence, progression, cancer-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 153 publications
0
12
0
Order By: Relevance
“…The summary of evidence supported that overweight or obesity (BMI ≥25 kg/m 2 ) is associated with an increased risk of both disease recurrence and progression for patients with nonmuscle-invasive bladder cancer. 68 Inconclusive results were noted with BMI and cancer site-specific mortality and all-cause mortality. Two cohort studies suggested that measurement of adiposity and muscle mass by computerized tomography (CT) scans, versus anthropometry, serve as better predictors of clinical outcomes in patients who undergo cystectomy because these measurements capture both fat and skeletal muscle mass.…”
Section: Genitourinary Cancersmentioning
confidence: 97%
See 1 more Smart Citation
“…The summary of evidence supported that overweight or obesity (BMI ≥25 kg/m 2 ) is associated with an increased risk of both disease recurrence and progression for patients with nonmuscle-invasive bladder cancer. 68 Inconclusive results were noted with BMI and cancer site-specific mortality and all-cause mortality. Two cohort studies suggested that measurement of adiposity and muscle mass by computerized tomography (CT) scans, versus anthropometry, serve as better predictors of clinical outcomes in patients who undergo cystectomy because these measurements capture both fat and skeletal muscle mass.…”
Section: Genitourinary Cancersmentioning
confidence: 97%
“…Indeed, sarcopenia was associated with an increased risk of all-cause mortality (HR, 1.67; 95% CI, 1.11-2.50), whereas BMI alone showed no association. 68 As acknowledged by the authors, the use of a single database (PubMed; and references of publications identified) was a limitation of their systematic review. Kidney cancer.…”
Section: Genitourinary Cancersmentioning
confidence: 99%
“…In relation to BC‐specific mortality, studies on the association with BMI and BP, respectively, have shown inconsistent results and are few 9,10 . Most of these studies were conducted among patients undergoing radical cystectomy, 11‐18 and fewer studies were conducted at population level 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Exercise is recommended to many patients with cancer in different clinical settings, however, there are no studies examining the effects of exercise in patients with NMIBC receiving intravesical therapy. 44 The patient with NMIBC group is older and has significant comorbidities that may make exercise more unsafe or less feasible compared with other patient with cancer groups. Moreover, no study to date has examined exercise during intravesical therapy.…”
Section: Discussionmentioning
confidence: 99%